2019
DOI: 10.1155/2019/9372563
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Chinese Medicine and Gut Microbiota in Chronic Constipation

Abstract: Chronic constipation is a common gastrointestinal dysfunction, but its aetiology and pathogenesis are still unclear. Interestingly, the compositions of the gut microbiota in constipation patients and healthy controls are different. Various studies reported the different gut microbiota alterations in constipation patients, but most studies indicated that constipation patients showed the decreased beneficial bacteria and the reduced species richness of gut bacteria. Besides, the alterations in the gut microbiota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
(64 reference statements)
0
18
0
Order By: Relevance
“…Gut bacteria play an important role in the digestion and absorption of nutrients in food and are considered as therapeutic targets of many diseases and drugs (30,31). It has become a hot research method in modern pharmacology to study the molecular mechanisms of drug treating diseases by focusing on gut bacteria (20,21). In order to further verify the potential mechanisms of VK2 for salt-sensitive hypertension, we supplemented VK2 to intervene high-salt induced mice, and detected the characteristics of gut bacteria by 16S rRNA analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Gut bacteria play an important role in the digestion and absorption of nutrients in food and are considered as therapeutic targets of many diseases and drugs (30,31). It has become a hot research method in modern pharmacology to study the molecular mechanisms of drug treating diseases by focusing on gut bacteria (20,21). In order to further verify the potential mechanisms of VK2 for salt-sensitive hypertension, we supplemented VK2 to intervene high-salt induced mice, and detected the characteristics of gut bacteria by 16S rRNA analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the roles in bowel motility, traditional CHMs can also play roles by interacting with intestinal flora and their metabolites. It has been demonstrated that CHMs can promote the proliferation and colonization of intestinal flora, while intestinal flora and their metabolites can promote the decomposition of CHM, but the exact mechanism needs to be confirmed by further basic experiments ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…This depends on subsequent further research including rectal manometry, colon transit time measurement, intestinal ora culture identi cation, etc. [6][7][8] . Since FRI does not belong to any kind of FGIDs, and the infant itself does not have any health problems, it is not ruled out as a normal physiological state [9] .…”
Section: Discussionmentioning
confidence: 99%